To determine morphometric analysis, vertical head diameter, foveal diameter, fovea transverse diameter, and foveal longitudinal diameter of the proximal femur in individuals from Central India - Dr.Asha Changil,Dr. Anjali patil,Dr. Rajendra singh (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background: The proximal femur, vital for human skeletal system, plays a vital role in hip joint biomechanical functions and is essential for medical and anthropological applications due to its anatomical dimensions. Aim: To determine the regional differences in this anatomical location by doing a thorough morphometric investigation of the vertical head diameter, foveal diameter, fovea transverse diameter, and foveal longitudinal diameter of the proximal femur.